(untitled) - Research Committee for Bicultural Life in Japan (Tokyo, 1985)
There are a few things to keep in mind to help your life in Japan to be smooth and ... some of the very basic information you will find useful in starting a new life in ... In order for you to reside in Japan, you will need a status of residence. ... foreign nationals with a mid- to long-term stay in Japan are issued a resident card.
Keywords: Nhật Bản,Japan; Mô tả và du hành,Description and travel